Sensitivity and Specificity of Urinary Ethyl Glucuronide and Ethyl Sulfate in Liver Disease Patients. (22nd June 2012) - Stewart, Scott H.; Koch, David G.; Burgess, Douglas M.; Willner, Ira R.; Reuben, Adrian
<x xml:space="preserve">Abstract</x> Background It is important to monitor alcohol use in the care of patients with liver disease, but patient self‐report can be unreliable. We therefore evaluated the performance of urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) in detecting alcohol use in the days preceding a clinical encounter. Methods Subjects (n = 120) were recruited at a university‐based hepatology clinic or during hospitalization. Alcohol consumption was ascertained by validated self‐report measures. Urine EtG (cutoff 100 ng/ml) and EtS (cutoff 25 ng/ml) concentrations were assayed by a contracted laboratory using tandem mass spectrometry. The sensitivity and specificity of each biomarker in the detection of drinking during the 3 and 7 days preceding the clinic visit were determined, as well as the influence of liver disease severity on these results. Results Urine EtG (sensitivity 76%, specificity 93%) and urine EtS (sensitivity 82%, specificity 86%) performed well in identifying recent drinking, and liver disease severity does not affect biomarker performance. After elimination of 1 false‐negative self‐report, urine EtG > 100 ng/ml was 100% specific for drinking within the past week, whereas 9% of the subjects without evidence of alcohol drinking for at least 1 week had EtS > 25 ng/ml. Conclusions Urine EtG and EtS can objectively supplement the detection of recent alcohol use in patients with liver disease. Additional research may determine optimal methods for integrating these tests into clinical care.